Consumer Perceptions of Product Lifetimes and Labelling: Implications for Introducing a Durability Label - Leonidas Milios; Carl Dalhammar (Circular Economy, 2023)
Extending the lifetime of products enables material resource savings and provides an effective resource efficiency strategy within a circular economy paradigm. Although consumer demand for longer lasting products that can be easily repaired has been on the rise, it is not certain that consumers are fully able to identify such products and willing to pay a premium for them. France introduced a mandatory product repairability index in 2021 and plans to introduce a mandatory product durability index by 2024. The reasoning was to allow consumers to benchmark products, and to provide incentives for manufacturers to design durable and repairable products. This initiative would most likely speed up activities for developing a harmonised European Union (EU) labelling scheme to avoid the possibility that various EU countries start their own schemes, which could be problematic for business within the EU single market. However, there is uncertainty regarding how to best display a durability label for influencing consumer choice. This contribution reviews the literature on product durability information and labelling, addressing consumer perceptions on durability labelling and whetherthe provision of durability information is taken into account in purchasing decisions. Potential implications in durability labelling implementation are discussed, concluding the article with suggestions for overcoming potential implementation challenges.